2008
DOI: 10.1158/1055-9965.epi-07-2523
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Intake and Risk of Pancreatic Cancer in Male Smokers (Finland)

Abstract: Extending research on the protective effect of flavonoids in cell culture and animal studies, we examined the association between consumption of flavonoids and flavonoid-rich foods and development of exocrine pancreatic cancer within the A-Tocopherol, B-Carotene Cancer Prevention Study cohort. Of the 27,111 healthy male smokers (50-69 years) who completed a selfadministered dietary questionnaire at baseline, 306 developed exocrine pancreatic cancer during follow-up (1985-2004; median, 16.1 years). Intakes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 48 publications
0
47
1
Order By: Relevance
“…Flavonoids hold great promise as agents to improve human health because epidemiological studies have shown protective effects associated with flavonoid consumption against coronary heart diseases (Arts and Hollman, 2005), stroke (Keli et al, 1996), and lung and colorectal cancers (Hirvonen et al, 2001;Bobe et al, 2008). Currently, several clinical trials are ongoing to test the anticancer efficacy of soy isoflavones and green tea, both of which contain flavonoids as the active ingredients (Crowell, 2005).…”
mentioning
confidence: 99%
“…Flavonoids hold great promise as agents to improve human health because epidemiological studies have shown protective effects associated with flavonoid consumption against coronary heart diseases (Arts and Hollman, 2005), stroke (Keli et al, 1996), and lung and colorectal cancers (Hirvonen et al, 2001;Bobe et al, 2008). Currently, several clinical trials are ongoing to test the anticancer efficacy of soy isoflavones and green tea, both of which contain flavonoids as the active ingredients (Crowell, 2005).…”
mentioning
confidence: 99%
“…A dietary pattern regarded as rich in flavonols was also found to decrease pancreatic cancer risk in smokers participating in the MEC study, but this was not confirmed in a validation study conducted within the EPIC cohort 19. Increasing intake of flavonoids also decreased pancreatic cancer risk in male smokers not consuming supplemental vitamins in the alpha‐tocopherol, beta‐carotene cancer prevention (ATBC) study ( n  = 306 cases) 14. Both were the only studies supporting an inverse association in smokers, which could be ascribed to the known anti‐oxidative effect (inhibition of CYP450 enzymes) elicited by flavonoids 4.…”
Section: Discussionmentioning
confidence: 96%
“…databases on flavonoids content in food, the number of food items used for the evaluation of intake of flavonoids, and whether the influence of food processing on flavonoids content was taken into consideration 12, 13, 15. In addition, in some studies, fewer flavonoids subclasses were considered to estimate intake of total flavonoids,9, 14, 16 while other studies focused on a single subclass,12, 17 and only few studies considered individual subclasses of flavonoids 14, 15, 18. Only the NIH‐AARP overcame most of these limitations by considering all subclasses of flavonoids (except proanthocyanidins), and accounting for flavonoids values of processed foods and recipes 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations